Magnetic curves in the generalized Heisenberg group. (January 2022) - Munteanu, Marian Ioan; Nistor, Ana Irina
Abstract: We study the magnetic trajectories in the generalized Heisenberg group H ( n, 1 ) of dimension ( 2 n + 1 ) endowed with its quasi-Sasakian structure. We prove that the trajectories are Frenet curves of maximum order 5 and we completely classify them.